2013
DOI: 10.1007/s10616-013-9580-4
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotective effect of soybean and sesame oils in ovariectomized rats via estrogen-like mechanism

Abstract: The purpose of the present study was to investigate the osteoprotective effects of soybean oil (SbO) and sesame oil (SO) in ovarictomized (OVX) rats. The results indicated that the OVX rats exhibited a significant decrease in Ca and P level in both serum and bone, the activities of the antioxidant enzymes SOD and CAT and the antioxidant biomarker GSH accompanied with a marked increase in the oxidative stress markers MDA and PC, the inflammatory indices (TNF-a, CRP levels, WBCs counts and ACP activity) in, both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 63 publications
3
21
0
Order By: Relevance
“…Our results are compatible with those reported by Riggs and Melton21 who found that menopause results in elevated bone turnover, an imbalance between bone formation and bone resorption and net bone loss, and this is attributed to the cessation of ovarian function and tapering off of estrogen secretion 2022. Also, the present work showed an increased level of serum OCN in ovariectomized rats.…”
Section: Discussionsupporting
confidence: 94%
“…Our results are compatible with those reported by Riggs and Melton21 who found that menopause results in elevated bone turnover, an imbalance between bone formation and bone resorption and net bone loss, and this is attributed to the cessation of ovarian function and tapering off of estrogen secretion 2022. Also, the present work showed an increased level of serum OCN in ovariectomized rats.…”
Section: Discussionsupporting
confidence: 94%
“…Ok HM et al also found that the femoral BMD of 8-week-old ovariectomized SD rats decreased significantly following feeding with a HFD (corn oil plus lard as dietary fat source) for eight weeks [ 35 ].Our result was different from those reports, which showed that the levels of BMD and BMC in the femur and lumbar vertebra as well as the femoral Ca content and bone mass in the OVX-HFD (soybean oil plus lard as dietary fat source) group were significantly increased as compared with the OVX rats. The reason was possibly related to the soybean oil, which was rich in omega-3 fatty acids and known to have the protective effect on osteoporosis [ 36 ]. The HFDD reduced the BMD and BMC levels in the femur and lumbar vertebra, and it also reduced the femoral Ca in both the SHFDD and OVX-HFDD groups, which suggested that a HFDD aggravates bone mass loss in normal and OVX rats ( Table 3 , Fig 3B ).…”
Section: Discussionmentioning
confidence: 99%
“…[186][187][188] A recent study elucidated that soybean oil (15% w/ w) have osteoprotective effect in ovariectomized rats which restored minerals, antioxidant enzymes, antioxidant biomarkers, oxidative stress markers, inflammatory indices, and white blood cells (WBCs) count altered due to the deficiency in the estrogen hormone. [189] Moreover, isoflavone administration 2560 could ameliorate the bone turnover resorption markers more efficiently in equol producing pre-as well as post-menopausal women and, therefore, exert anabolic effect on the bones. [190] Relation between intake of isoflavones and BMD at the lumbar spine (LS) and femoral neck (FN) in different racial/ ethnic groups viz.…”
Section: Isoflavones and Osteoporosismentioning
confidence: 99%